Multi-Organ Dysfunction in Cerebral Palsy - Allen, John; Zareen, Zunera; Doyle, Samantha; Whitla, Laura; Afzal, Zainab; Stack, Maria; Franklin, Orla; Green, Andrew; James, Adam; Leahy, Timothy Ronan; Quinn, Shoana; Elnazir, Basil; et al. (Frontiers in Pediatrics, 2021)
Cerebral Palsy (CP) describes a heterogenous group of non-progressive disorders of posture or movement, causing activity limitation, due to a lesion in the developing brain. CP is an umbrella term for a heterogenous condition and is, therefore, descriptive rather than a diagnosis. Each case requires detailed consideration of aetiology. Our understanding of the underlying cause of CP has developed significantly, with areas such as inflammation, epigenetics and genetic susceptibility to subsequent insults providing new insights. Alongside this, there has been increasing recognition of the multi-organ dysfunction (MOD) associated with CP, in particular in children with higher levels of motor impairment. Therefore, CP should not be seen as an unchanging disorder caused by a solitary insult but rather, as a condition which evolves over time. Assessment of multi-organ function may help to prevent complications in later childhood or adulthood. It may also contribute to an improved understanding of the aetiology and thus may have an implication in prevention, interventional methods and therapies. MOD in CP has not yet been quantified and a scoring system may prove useful in allowing advanced clinical planning and follow-up of children with CP. Additionally, several biomarkers hold promise in assisting with long-term monitoring. Clinicians should be aware of the multi-system complications that are associated with CP and which may present significant diagnostic challenges given that many children with CP communicate non-verbally. A step-wise, logical, multi-system approach is required to ensure that the best care is provided to these children. This review summarises multi-organ dysfunction in children with CP whilst highlighting emerging research and gaps in our knowledge. We identify some potential organ-specific biomarkers which may prove useful in developing guidelines for follow-up and management of these children throughout their lifespan